Resistance pattern of methicillin resistant Staphylococcus aureus among nasal isolates of HIV infected patients in a tertiary care hospital - Diwakar, Manish Kumar; Goyal, Ankur; Goyal, Sapna (International Journal of Research in Medical Sciences, 2019)
Background: Patients infected with HIV have an increased risk of nasal Staphylococcus aureus carriage as well as consecutive staphylococcal infections and is a major reservoir for MRSA which is potential risk factors for community acquired MRSA. Knowing the Nasal carriage status of Staphylococcus aureus and their Antibiogram will be beneficial for effective management of these patients. Methods: Nasal swab sample were collected from all the participants and processed for culture and identification of Staphylococcus aureus and their antimicrobial sensitivity. All the Staphylococcus aureus isolates were tested for Methicillin resistance by Oxacillin screen agar test, cefoxitin disc diffusion test and further confirmed by mecA gene PCR. Results: In this study out of 220 HIV seropositive patients, 43.64% isolates were confirmed to be S. aureus, 18.75% MRSA and 81.25% were MSSA. Cefoxitin disc diffusion showed 100% specificity (95% CI; 97.05%-100.00%), 100% sensitivity (95% CI; 83.89-100.00%) and 100% accuracy (95% CI; 97.47% to 100.00%) while comparing with gold standard mecA gene PCR. Among the nasal carriers; males (60%) ware dominant on females (40%). 31-50 years age group was strongly associated with MRSA nasal carriage. None of the isolates were resistant against lenozolid, teicoplanin and vancomycin while ampicillin (75%), ciprofloxacin (62.5%), clindamycin (59.38%) and cotrimoxazole (53.13%) showed increased resistance against S. aureus nasal carriage. Conclusions: Resistance among HIV positive persons for all antibiotics showed statistically significant while compared to control group. Cefoxitin disc diffusion can be used as surrogate agent for mecA gene detection.